Stability and transformation of jarosite and Al-substituted jarosite in an acid sulfate paddy soil under laboratory and field conditions - Andrew R.C. Grigg; Worachart Wisawapipat; Kurt Barmettler; Katrin Schulz; Luiza Notini; ThomasArrigo, Laurel; Ruben Kretzschmar (My University, 2024)
Jarosite, a prominent mineral in oxidised acid sulfate soil, is known to sorb and incorporate a variety of elements, including Al. However, to understand the role that jarosite plays in regulating element cycles, it is crucial to understand the stability and transformation pathways of jarosite in an acid sulfate soil under dynamic biogeochemical conditions. In this study, we observed the transformation of unsubstituted jarosite and Al-substituted jarosite, collectively referred to as ‘jarosite’, in an acid-sulfate rice paddy topsoil and subsoil from Thailand. Jarosite was incubated in flooded paddy topsoils and subsoils for up to sixteen weeks, both in laboratory mesocosms and in the field, using bags made of polyethylene terephthalate mesh. One set of mesh bags contained jarosite that was not mixed with any other minerals, and referred to as ‘pure mineral’ incubations. Mineral transformations occurred under the influence of the soil porewater only and were primarily followed by X-ray diffraction analysis. A parallel set of mesh bags contained soil with 57Fe-labelled jarosite enrichment (Fe enriched in soil by a factor of 1.3 but 57Fe enrichment factor of 12.5–13.6), which allowed jarosite transformation to occur in close association with the soil matrix. Mineral transformations in 57Fe-jarosite-enriched soil were followed using 57Fe Mössbauer spectroscopy. In laboratory mesocosms and in the field, jarosite transformed most quickly in topsoil, whereas jarosite underwent limited transformation in subsoils, especially in laboratory mesocosms where Fe reduction was slow. The chemical environment around the jarosite affected the outcome of the transformation processes. Crystalline Fe oxyhydroxides, such as goethite, dominated the products in mesh bags where jarosite was not mixed with soil, whereas short-range-ordered or non-mineral Fe phases, such as Fe(II) sorbed to mineral surfaces or complexed with organic ligands, were dominant transformation products of jarosite when mixed in soil. Furthermore, Al substitution in jarosite caused contrasting effects in mesh bags containing pure minerals or mineral-enriched soil. Aluminium substitution slowed the transformation of jarosite in pure mineral mesh bags, but Al-substituted and unsubstituted jarosite showed similar transformation rates and pathways when incubated as a mixture with soil. The contrasting rate of transformation in topsoil and subsoil, the contrasting products of transformation in pure mineral mesh bags and 57Fe-jarosite-enriched soil, and the contrasting effect of Al substitution in pure mesh bags or jarosite-enriched soil, all demonstrate that the rate and products of jarosite transformation are defined by a balance between competitive transformation pathways that affect the transforming minerals.
Keywords: Iron minerals; Mössbauer spectroscopy; Redox; Rice paddy; Soil incubation